Dermoscopic (Onychoscopic) findings of various nail disorders among patients attending dermatology-teaching center in Sulaymaniyah city - Paiman Ahmed Kwekha Qadir; Ali Mozan Dhahir Elethawi (Advanced Medical Journal)
Background and objectives: The term onychoscopy have recently been introduced to define the use of dermoscopy in nail disorders, which is the dermoscopic examination of nail unit and its components. With onychoscopy, many nail signs can be magnified and combined with clinical examination to reach a diagnosis, it aids in avoiding the need of nail biopsy. Aim of this study is to describe the onychoscopic features of the most important nail disorders.